Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/cmdc.201000253
|View full text |Cite|
|
Sign up to set email alerts
|

Design and Synthesis of Selective and Potent Orally Active S1P5 Agonists

Abstract: The immunomodulatory drug fingolimod (FTY720, 2-amino-2-[2-(4-octylphenyl)ethyl]propane-1,3-diol), derived from a fungal metabolite myriocin), is phosphorylated in vivo by sphingosine kinases to produce (R)-FTY720-phosphate (FTY720-P). [1,2] FTY720-P activates sphingosine-1-phosphate (S1P) receptors S1P1, S1P3, S1P4, and S1P5 at low nanomolar concentrations and is inactive toward the S1P2 receptor.[1] The FTY720-P-mediated activation of the S1P1 receptor on lymphocytes induces receptor internalization, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Here, for the first time, we showed that psychosine can directly induce a concentration-dependent demyelination, as expressed by a decrease in the levels of MOG, PLP and MBP, and that pFTY720 can attenuate these effects. These findings are in agreement with our and other previous reports demonstrating that pFTY720 rescues myelination (Coelho et al, 2007;Jung et al, 2007;Mattes et al, 2010;Miron et al, 2008a,b;Sheridan and Dev, 2012). Interestingly, unlike LPC, psychosine treatment alone did not induce the release of IL6, TNFα or IL1β from cerebellar slices, which was in agreement with our astrocyte data.…”
Section: Discussionsupporting
confidence: 94%
“…Here, for the first time, we showed that psychosine can directly induce a concentration-dependent demyelination, as expressed by a decrease in the levels of MOG, PLP and MBP, and that pFTY720 can attenuate these effects. These findings are in agreement with our and other previous reports demonstrating that pFTY720 rescues myelination (Coelho et al, 2007;Jung et al, 2007;Mattes et al, 2010;Miron et al, 2008a,b;Sheridan and Dev, 2012). Interestingly, unlike LPC, psychosine treatment alone did not induce the release of IL6, TNFα or IL1β from cerebellar slices, which was in agreement with our astrocyte data.…”
Section: Discussionsupporting
confidence: 94%
“…These effects may be attributed to an enhanced survival of mature oligodendrocytes and/or stabilization of the myelin sheath. In previous studies we have shown that pFTY720 increases the number of MBP-positive mature oligodendrocytes (Mattes et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…We have also previously demonstrated that S1PR activation increases the number of MBP-positive mature oligodendrocytes in culture (Mattes et al, 2010). Here, using organotypic cerebellar slices, we determine the role of S1P1Rs in demyelination.…”
Section: Introductionmentioning
confidence: 81%
“…However, there is currently no evidence to support this notion. Although some selective and orally active S1PR5 agonists have been synthesized 104 , their in vivo effects have not yet been reported.…”
Section: Targeting Other S1prsmentioning
confidence: 99%